Kepercayaan dan Pertentangan Ideologi dalam Cerpen “Cerita Lama Negara Suka dan Negara Neka” Karya Jelsyah Dauleng (Kajian Hegemoni Gramsci) - Falah, Fajrul (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
This study aims to revealed the beliefs and ideological contradictions in the short story “Cerita Lama Negara Suka dan Negara Neka” creation Jelsyah Dauleng. This research is based on fictional thoughts and ideas (short story) is a reflection of the writer's thoughts to the world of reality of the people being referred. Language and symbols in the short story, meaningful that needs to be expressed. The object of this research material is short story “Cerita Lama Negara Suka dan Negara Neka” published by Harian Haluan, 10 February 2019. This study uses a sociological approach, to reveal issue and social aspects contained in the short story, specifically enter the realm of Gramsci's hegemony. The research method used is descriptive qualitative. Research data obtained from the short story text (words, phrases, sentences) that are relevant to Gramsci's ideology, beliefs, social aspects and hegemony. The research data is then interpreted according to the approach used, then presented descriptively. The results of the research on this short story showed that there was a conflict between group members then each group separated and created their respective countries. Conflict and the separation of the two countries Successfully muted because of group members Negara Neka trust belief Negara Suka, namely a life full of peace, kindness, and other realms. Trust Negara Neka to Negara Suka finally fade after a disaster. Group Negara Neka returned to the ideology it believed.